â€œBREAD & ROSESâ€: SOCIOLOGICAL ANALYSIS OF LITERATURE AND ITS RELEVANCE TO THE PRESENT IN THE CONTEXT OF THE WORKING CLASS - Faza Fauziyyah (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2023)
The article